Imaging Spectrum of Lobular Carcinoma In Situ and Correlation with Pathology Findings - Hande, Pradipta C; Arneja, Sarabjeet Kaur; Desai, Sabita S (Indian Journal of Radiology and Imaging, 2021)
Background Lobular carcinoma in situ (LCIS) is a noninvasive neoplasm that is known to have an increased relative risk for developing subsequent invasive breast carcinoma. Pure LCIS is usually an incidental finding on histopathological examination (HPE) of tissue samples. However, in the recent years, there has been an increasing trend seen in the diagnosis of LCIS.Purpose This article aims to bring out the spectrum of appearances on breast imaging in confirmed cases of pure LCIS on HPE and immunohistochemical.Materials and Methods Cases that were confirmed as pure LCIS on HPE from core or excision biopsy were retrospectively analyzed for abnormalities on breast imaging. Digital breast tomosynthesis mammography was performed with high-resolution ultrasound with elastography for all cases. Magnetic resonance imaging (MRI) was performed in cases wherever indicated, with dynamic postcontrast imaging after injecting intravenous gadolinium.Conclusion LCIS is recognized as an intermediate risk factor for the development of breast cancer. Pure LCIS has varied histology and imaging patterns on mammography, high-resolution ultrasound, and MRI. It is important to recognize the imaging appearances of these lesions to enable the radiologist to detect LCIS early for proper management.
Keywords: architectural distortion; digital breast tomosynthesis; hook-wire localization; immunohistochemistry; lobular carcinoma in situ; microcalcifications